Analysis of Factors Associated With Variability and Acidosis of the Umbilical Artery pH at Birth - María Luisa Mayol Pérez; María Luisa Mayol Pérez; José Manuel Hernández Garre; José Manuel Hernández Garre; Paloma Echevarría Pérez (Frontiers Media S.A., 2021)
Background: Perinatal asphyxia is a significant contributing factor for neonatal morbidity and mortality. The aim of this study was to investigate the clinical factors associated with umbilical artery pH variability and fetal acidosis at birth.Methods: This is a single center cross-sectional study in a public regional hospital in southeastern Spain from January to December 2019. The reference population was 1.655 newborns, final sample of 312 experimental units with validated values of umbilical cord blood pH.Results: Factors such as gestational age at term (X̄at-term: 7.26 ± 0.08-X̄no-at−term: 7.31 ± 0.05, p: 0.00), primiparity (X̄primiparity: 7.24 ± 0.078-X̄multiparity: 7.27 ± 0.08, p: 0.01), induced labor (X̄induced: 7.24 ± 0.07-X̄spontaneous: 7.26 ± 0.081, p: 0.02), vaginal delivery (X̄vaginal:7.25 ± 0.08-X̄cesarean:7.27 ± 0.07, p: 0.01), and prolonged dilation duration (X̄AboveAverage: 7.22 ± 0.07-X̄BelowAverage: 7.27 ± 0.08, p: 0.00), expulsion duration (X̄AboveAverage: 7.23 ± 0.07-X̄BelowAverage: 7.26 ± 0.08, p: 0.01), and total labor duration (X̄AboveAverage: 7.23 ± 0.07-X̄BelowAverage: 7.27 ± 0.08, p: 0.00) are associated with a decrease in umbilical artery pH at birth. However, only three factors are associated with acidosis pH (<7.20) of the umbilical artery at birth: the induction of labor [OR: 1.74 (95% CI: 0.98-3.10); p: 0.04], vaginal delivery [OR: 2.09 (95% CI: 0.95-4.61); p: 0.04], and total duration of labor [OR: 2.06 (95% CI: 1.18-3.57); p: 0.01].Conclusions: Although several factors may affect the variability of umbilical artery pH at birth by decreasing their mean values (gestational age, primiparity, induced labor, vaginal delivery and prolonged: dilation duration, expulsion duration and total labor duration), only induction of labor, vaginal delivery and total duration of labor are associated with an acidosis (<7.20) of same.